2018
DOI: 10.4149/neo_2018_171225n841
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CRNDE may be associated with poor prognosis by promoting proliferation and inhibiting apoptosis of cervical cancer cells through targeting PI3K/AKT

Abstract: Long non-coding RNAs (lncRNAs) are attracting more and more attention from researchers because they are relatively new factors in regulating biological processes in human cancers. The Colorectal Neoplasia Differentially Expressed (CRNDE) lncRNA is transcribed from chromosome 16 on the opposite strand to the neighboring IRX5 gene. It was originally discovered abnormally expressed in colorectal cancer (CRC) and was certified a critical biomarker in many cancers. However, its biological function and mechanism und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…29 Similar with our ndings, CRNDE regulated PI3K/AKT pathway, and thus exerted oncogenic function in cervical cancer. 12 CRNDE promoted the progression of gastric cancer through regulating PI3K/AKT pathway. 30 Moreover, CRNDE activated PI3K/AKT signaling to promote tumor cell proliferation and growth in non-small cell lung cancer, highlighting it role as a potential novel therapeutic target for this disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…29 Similar with our ndings, CRNDE regulated PI3K/AKT pathway, and thus exerted oncogenic function in cervical cancer. 12 CRNDE promoted the progression of gastric cancer through regulating PI3K/AKT pathway. 30 Moreover, CRNDE activated PI3K/AKT signaling to promote tumor cell proliferation and growth in non-small cell lung cancer, highlighting it role as a potential novel therapeutic target for this disease.…”
Section: Discussionmentioning
confidence: 96%
“…PI3K/AKT pathway was demonstrated to be involved in CRNDE-mediated pro-tumor effect in some cancers. 12 Moreover, we conrmed that the inactivation of PI3K/AKT/mTOR pathway inhibited the proliferation, migration and invasion, and promoted apoptosis in TSCC cells (ESI Fig. 1 †).…”
Section: Crnde Regulated Pi3k/akt/mtor Pathway In Tscc Cellsmentioning
confidence: 88%
“…The interactions between ncRNAs and PI3K signaling in cancer have been studied. For example, the lncRNA CRNDE which promote cell proliferation through activating PI3K signaling, is highly expressed in patients with non-small cell lung cancer, colorectal cancer, gastric cancer, cervical cancer, heptaocellular carcinoma and gallbladder cancer [60][61][62][63][64][65]. In addition to activating PI3K pathway, some ncRNAs have been reported to inhibit the activity of PI3K signaling.…”
Section: Non-coding Rna and Other Factors In Regulation Of Pi3k Pathwaymentioning
confidence: 99%
“…In particular, the mutations of PIK3CA E542K and E545K promote glycolysis and proliferation of CC in vitro and vivo [212]. NBPF1, ARHGAP17, miR-99b, -181a2/181b2, -338, -383, -433 and -489, as well as LncRNA ANRIL, CRNDE, NEAT1 and LINC01305 are involved in the proliferation, invasion, autophagy or EMT via PI3K/AKT pathway [213][214][215][216][217][218][219][220][221][222][223][224]. Currently, only preclinical trials of PI3K inhibitor LY294002 has revealed it significantly radiosensitized CC cell lines in vitro and vivo [225,226], and the terminated clinical trials of AKT inhibitor GSK2141795 (NCT01958112, Table 3) has tried to display a novel treatment approach to patients of CC.…”
Section: Nct02240212mentioning
confidence: 99%